Incidence, Severity, and Outcomes of Acute Kidney Injury in Octogenarians following Heart Valve Replacement Surgery - Michael A. Mao; Charat Thongprayoon; YiFan Wu; Vickram Tejwani; Myriam Vela-Ortiz; Joseph Dearani; Qi Qian (International Journal of Nephrology, 2015)
Background. The study investigates the occurrence, severity, and outcomes of acute kidney injury (AKI) in octogenarians following heart valve surgery. Methods. All patients, age >80 years, not on dialysis and without kidney transplant, undergoing heart valve replacement at Mayo Clinic, Rochester, in the years 2002-2003 were enrolled. AKI was diagnosed based on AKIN criteria. Results. 209 octogenarians (88.0% aortic valve, 6.2% mitral valve, 1.0% tricuspid valve, and 4.8% multivalve) with (58.4%) and without CABG were studied. 34 (16.3%) had preexisting CKD. After surgery, 98 (46.8%) developed AKI. 76.5% of the AKI were in Stage 1, 9.2% in Stage 2, and 14.3% in Stage 3. 76.5% CKD patients developed AKI. Length of hospital stay was longer for AKI patients. More AKI patients were discharged to care facilities. Patient survival at 30 days and 1 year for AKI versus non-AKI was 88.8 versus 98.7%, p=0.003, and 76.5 versus 88.3%, p=0.025, respectively. With follow-up of 3.94±0.28 years, Kaplan-Meier analysis showed a reduced survival for AKI octogenarians. Preexisting CKD and large volume intraoperative fluid administration were independent AKI predictors. Conclusions. Nearly half of the octogenarians developed AKI after valve replacement surgery. AKI was associated with significant functional impairment and reduced survival.